A CASE STUDY ON THE DEVELOPMENT OF A SCRUM AND DEVOPS APPLICATION - Podgornik, Hygor; Gibertoni, Daniela (Revista Interface Tecnológica, 2020)
The market constantly changes to meet the needs of users, and constantly the needs of users change and with this, no software will have the requirements very well defined right at the beginning of the project, as they are constantly changing. Thus, it becomes necessary that software development is not limited to development methodologies that do not allow such changes. To solve this problem, agile development methodologies have emerged, which allow teams to be self-managing and self-adaptable to needs, making changes less costly. However, development is a part of the process, and it still depends on the operations team for applications to be published correctly, and the operations team also felt the need to make the infrastructure agile. With that, DevOps emerged, a cooperation between the development team and the operations team, so that not only was the development team agile in developing needs, but the operations team could also be agile when delivering them to the end user, so that there is still a quality in the product being delivered. This article addresses, through experimental exploratory bibliographic research, the experience of an academic scrum team applying the DevOps culture during the development of an application for a philanthropic institution. As main results obtained, we highlight a higher quality of the published product and a greater motivation of the team to see every week that their work was being published on the internet.
Keywords: Agile Development; Scrum; DevOps; Web applications; Operations